Impact of Cashless Transaction on Business: A Case of Kathmandu Valley - Kathbanya, Suraj Das (Nepalese Journal of Finance, 2025)
This study examines the impact of cashless transaction on business: A case of Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are security, ease of use, fastest transaction, perceived benefit, and accessibility. The primary source of data is used to assess the opinions of respondents regarding security, ease of use, fastest transaction, perceived benefit, accessibility, and customer satisfaction. The study is based on primary data of 129 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of cashless transaction on business: A case of Kathmandu Valley. The study showed a positive impact of security on customer satisfaction. It indicates that higher the security of cashless transaction leads to increase in customer satisfaction. Similarly, the study showed a positive impact of ease of use on customer satisfaction. It indicates that higher the ease of use, higher would be the customer satisfaction. Likewise, the study also revealed a positive impact of perceived benefit on customer satisfaction. It indicates that individual’s belief that specific positive outcomes will result higher the customer satisfaction. Further, the study observed a positive impact of accessibility on customer satisfaction. It indicates that higher the accessibility of cashless transaction and digital payment on business, higher would be the customer satisfaction. In addition, the study observed a positive impact of fastest transaction on customer satisfaction. It indicates that quick transaction leads to increase in customer satisfaction.